Development of Mobile Application-Based Early Childhood Education and Elementary School Transition Guidelines for Parents - Dinda Robayanti; Heny Djoehaeni; Mubiar Agustin (STAI Hubbulwathan Duri, 2024)
This study addresses the critical transition from Early Childhood Education (PAUD) to Elementary School (SD), focusing on the development of a mobile application to support parents during this phase. The transition significantly impacts children’s social, emotional, and cognitive readiness. Conducted in Babakan Ciparay, Bandung, the study employs the Research and Development (RD) method using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) framework. The sample consists of 150 parents of children in group B kindergarten/RA/equivalent and grades 1–2 SD/MI/equivalent, representing the transition phase. In-depth interviews were conducted with six parents to gather qualitative insights. Over 50% of parents demonstrated awareness of the PAUD-SD transition, but their understanding highlighted a need for accessible digital guidance, often sourced from the internet. These insights informed the creation of the PAUD.int application. Evaluation using the Technology Acceptance Model (TAM) and System Usability Scale (SUS) indicated high usability and acceptance of the app, confirming its effectiveness in supporting parents during this transition. The PAUD.int application has the potential to improve children's readiness and enhance parental engagement during the transition. However, challenges such as device compatibility and registration processes suggest opportunities for technical and functional enhancements. The development of the PAUD.int application demonstrates the value of digital tools in facilitating smoother PAUD-SD transitions. Future studies should explore further technical improvements and interactive features to expand its impact on parental support and child readiness.